Screening for risk factors associated with non-specific shoulder pain in mail adolescent water polo players - Tully, Paula Lauren (Department of Health and Rehabilitation Sciences, 2023)
Water polo is a fast-growing aquatic sport that combines swimming, overhead throwing, defending and grappling. There are great demands placed on the shoulder to complete these activities and shoulder pain is the most common musculoskeletal complaint among water polo players. The aetiology of shoulder injury amongst water polo players is not well understood and there is limited research investigating the adolescent water polo population. The aim of this thesis was to identify the incidence of shoulder pain over a 12-week period and determine the contribution of intrinsic and extrinsic risk factors in the development of non-specific shoulder pain in male adolescent water polo players. An overview of the literature (Chapter 2) includes the biomechanics of throwing and swimming; the epidemiology of shoulder injury in water polo players; and the current understanding of risk factors for shoulder injuries and the screening thereof. Risk factors for shoulder injury in swimming have been identified as weakness of the glenohumeral (GH) internal rotator muscles, altered GH range of motion (ROM), GH joint laxity, high training loads, pectoralis minor tightness and altered scapular control. In other overhead throwing sports the risk factors include altered GH ROM and glenohumeral internal rotation deficit (GIRD), shoulder muscles weakness, altered scapular control, pitching velocity, age, height, early sport specialisation, throwing with arm fatigue and a heavy workload. A few studies have proposed potential risk factors for shoulder injury in water polo players but significant associations have not been found and little is known about the musculoskeletal risk factors. However, water polo players are susceptible to shoulder pain due to repetitive overheard throwing at high velocities, the repetitive swimming stroke as well as the unique upright swimming style. Chapter 3 presents the research findings. This study recruited male adolescent water polo players between the ages of 14-18 who were not currently experiencing shoulder pain. Participants underwent a pre-season screening session followed by a period of in-season monitoring for 12 weeks. The pre-season screening included a demographic questionnaire, the Kerlan-Jobe Orthopaedic Clinic (KJOC) Shoulder and Elbow Score, anthropometry and maturation testing as well as shoulder specific tests to assess for shoulder pain, shoulder range of movement, shoulder strength, shoulder flexibility and shoulder stability. The experience of shoulder pain and participant training load was then monitored using a selfreport questionnaire. Participants were categorised into two groups (shoulder pain and no shoulder pain) based on their report of pain, irrespective of a medical diagnosis. The shoulder musculoskeletal profile of the water polo players, the incidence of shoulder pain and the player's training loads are presented (Chapter 3). Shoulder pain was reported by 52% of the participants at least once during the 12-week monitoring period, with pain in both the shoulders simultaneously (56%) or the dominant shoulder only (42%) commonly reported. The onset of activity was reported most commonly as swimming (55%) followed by throwing (38%). Participants with shoulder pain had mean KJOC scores lower than 90, and were significantly older (p = 0.003), heavier (p = 0.050) and the predicted years from peak height velocity (PHV) was greater (p = 0.029) than those without shoulder pain. An interaction was found between pain/no pain and dominant/non-dominant side for isometric internal rotation (IR) strength (p = 0.049), with stronger IR muscles in the dominant shoulder of the group with shoulder pain. Significant shoulder asymmetries were identified, however there was no association between the variables and the development of shoulder pain. In general, the participants presented with greater external rotation (ER) ROM and total range of motion (TROM) in the dominant shoulder, greater isometric strength of the IR muscles, serratus anterior (SA), upper trapezius (UT) and lower trapezius (LT) muscles, as well as reduced pectoralis minor length (PML) and a lower pectoralis minor index (PMI) on the dominant side. There was a significant difference between pain/no pain and the hours of water polo matches in weeks 3-4, with a higher work load in the shoulder pain group compared to the no shoulder pain group (p = 0.008). Participants with shoulder pain reported significantly lower selfperceived strength scores for passing, shooting, swimming, defending and gym training compared to those without shoulder pain. In conclusion (Chapter 4), there is a high incidence of shoulder pain among male adolescent water polo players, which is in line with the findings from other studies. The players who developed shoulder pain were significantly older, heavier and had a higher predicated age from PHV than those without shoulder pain. This may suggest a trend towards cumulative overloading and it's likely that the key players of water polo teams may be at greater risk of developing shoulder pain. Greater IR strength was observed in the dominant shoulder of those players with shoulder pain, indicating that the more powerful throwers are developing shoulder pain. The relative weakness of the ER muscles suggests that players are unable to effectively control through deceleration of the throwing motion. This cohort presented with significant asymmetries in GH ROM, rotator and scapular muscle strength, and shoulder flexibility; however, these variables were not associated with shoulder pain. Asymmetries have been associated with pain in previous studies, so these variables should not be ruled out as risk factors for injury. Participants of this study reported the activity most commonly associated with shoulder pain was swimming, not throwing, and bilateral shoulder pain was commonly reported. This would suggest that the musculoskeletal profile of the non-dominant side is indeed important and that the implications of significant asymmetries should be evaluated further in a larger population. KJOC scores seem to be in line with those for baseball players and a score below 90 may indicate an at-risk athlete. An increase in competitive match play was associated with an increase in shoulder pain. This should inform coaches to structure training and recovery appropriately during tournaments or weeks with a high load of matches. This study provides a basis for further investigation into shoulder injuries among adolescent water polo players, as well as the prevention and management thereof. It is advised that coaches and medical staff endeavour to identify at-risk players. Rehabilitation programs should be implemented to target the modifiable risk factors identified in this study, in order to reduce the incidence and prevalence of shoulder pain.